Analysis of Individual and Environmental Factors for Road Traffic Accidents in Sirjan-Bandarabbas Road between 2010 and 2011, Iran - Ghorbanali Mohammadi; Darius Mohammadi (Iranian Journal of Health, Safety and Environment, 2016)
Sirjan -Bandarabbas road is one of the important commercial roads in Iran and for Sirjan's area situation and relevance between Sirjan and other states in Iran so high percentage of goods that forwarded from Bandarabbas to other states transit from Sirjan .Therefore this road is as one important transition road and traffic road too .This study analyzed road traffic accidents were occurred between 2010 and 201in Sirjan- Bandarabbas road. Individual and demographic factors include Time of accidents, Drivers age, time of the days, seat belt and safety laws, Guilty vehicle, Mode of accident and education Level. Time of day analyses suggested that the highest percentage of road traffic injuries occurred in the time group between 12-18 hours. Drivers with the age group of 36-50 had more involvement in death accidents. The findings of this study also revealed that most of the collisions was front to back and front to side. Female drivers were found to be generally safer drivers than their male counterparts; male drivers had a higher involvement rate in road traffic accidents. This study indicated that Observe safety laws, Guilty vehicle and Mode of accidents have a meaningful relationship with Type of accidents in road traffic accidents in Sirjan Bandarabbas road.